RECRUITMENT POLICY OF CIVIL SERVANT CANDIDATES OF THE MINISTRY OF EDUCATION, CULTURE, RESEARCH, AND TECHNOLOGY FOR DIASPORA APPLICANTS WITH INDONESIAN CITIZENSHIP: KEBIJAKAN REKRUTMEN CPNS KEMENDIKBUDRISTEK TERHADAP PELAMAR DIASPORA BERKEWARGANEGARAAN INDONESIA - Putra Pratama, Nawangga; Antikowati, Antikowati; Tua Sagala, Christo Samurung (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2024)
In this study, researchers used the Yuridis-Normative legal research and writing methodology by using 3 (three) approaches, including conceptual approaches, statutory approaches, and comparative approaches. This research discusses the opportunities for Diaspora with Indonesian citizenship in the recruitment of Civil Servant Candidates for the Ministry of Education, Culture, Research and Technology. The legal issues raised in this research are as Diaspora with Indonesian citizenship are part of Indonesian citizens who are constitutionally valid so that their rights and obligations apply absolutely based on the 1945 Constitution of the Republic of Indonesia. The issues discussed are the recruitment mechanism to accommodate the participation of Indonesian Diaspora who apply in the general formation and the continuation of studies for Diaspora who have passed the CPNS recruitment. Moreover, in this case, the Diaspora is not regulated in general formations, but special formations.